Determine if intra-axonal mRNA translation occurs at discrete “hot spots” during synapse formation - Trigo, Guilherme Gomes (2021)
The human nervous system is composed of an intricate and complex neuronal network. Synapses are the building blocks of this network and so a correct formation of the pre- and postsynaptic terminal is necessary, which is driven by a dynamic organization of proteins in locu. Intra-axonal mRNA translation has been shown to provide the proteins necessary for axonal growth and pathfinding. However, it is still unclear how local protein synthesis regulates presynaptic formation. To address this question, we cultured rat embryonic hippocampal neurons in microfluidic chambers. These devices allow the physical and fluidic isolation of distal axons and, thus, allow the study of axonal intrinsic mechanisms. We found that intra-axonal mRNA translation is required for presynaptic differentiation. We further observed that presynaptic differentiation induced by fibroblast growth factor 22 and Poly-D-Lysine-coated beads is accompanied by an increase of translational markers in newly formed presynaptic sites. Together, these results demonstrate the existence of local intra-axonal mRNA translation during synapse formation.